‘Kinship like I've never experienced before’: Modern mechanical solidarity on the Appalachian trail network - Samantha B. Cake; JoEllen Pederson (Social Sciences and Humanities Open)
Emile Durkheim (1858–1917) believed that mechanical solidarity–a type of social solidarity that emerges from the homogeneity of actors' social realities–is only able to flourish in traditional societies. The current study challenges that assertion by demonstrating that in modern-day America, mechanical solidarity plays a prominent role in creating the uniquely generous, trusting culture in the thru-hiking community of the Appalachian Trail (A.T.) network. This mixed-methods study used 10 semi-structured, ethnographic interviews and 97 survey questionnaire responses from current or former thru-hikers of the A.T. network. Hikers indicated in survey data that they see themselves as part of a hiking community. All respondents reported valuing collective trust, mutual respect, generosity, emotional support; and engaging in community-minded practices. Respondent's collective values, along with the common environment and shared goals that they possess as thru-hikers, produce a sense of collective consciousness–and thus, mechanical solidarity–in the thru-hiking community of the A.T. network.